Managing Psoriatic Arthritis With Different Types of Physical Activity: A Literature Review - Anna Wisniewska; Karina Lissak; Bianka Nowińska; Wiktoria Bińczyk; Bartosz Siudek; Olgierd Dróżdż; Julia Wierzbińska; Natalia Rutecka (Nicolaus Copernicus University in Toruń, 2024)
Up to 30% of people with psoriasis may develop psoriatic arthritis (PsA), a complicated inflammatory disease characterized by skin signs, joint discomfort, and swelling. Although pharmaceutical therapies have been the primary component of traditional PsA care, the advantages of physical activity are becoming more widely acknowledged. This review looks at how exercise can help manage PsA, with particular emphasis on several types of exercise, including resistance training, functional training, aerobic training, and high-intensity interval training (HIIT). Research indicates that resistance training increases muscle strength and functional ability while aerobic exercise lessens tiredness and musculoskeletal pain. Without escalating disease activity, HIIT reduces fatigue and enhances cardiorespiratory fitness. The review also looks at the relationship between physical activity and PsA symptoms including enthesitis and bone marrow edema (BME). Research shows that exercise does not worsen BME, and even if it can cause enthesitis, the advantages of exercise in terms of lowering overall disease activity and enhancing quality of life exceed the dangers. To sum up, customized exercise regimens are crucial for PsA management and have a major positive impact on patient well-being and disease control.